Laboratory Maintenance and Culture of Pseudogymnoascus destructans, the Fungus That Causes Bat White‐Nose Syndrome. Issue 1 (26th January 2021) - Blehert, David S.; Lorch, Jeffrey M.
Abstract: Pseudogymnoascus destructans is a fungal pathogen that causes white‐nose syndrome, an emerging and fatal disease of North American bats that has led to unprecedented population declines. As a psychrophile, P. destructans is adapted to infect bats during winter hibernation, when host metabolic activity and core body temperature are greatly reduced. The ability to maintain and cultivate isolates of P. destructans in the laboratory is necessary for conducting research with this fungus. This article describes protocols for culturing P. destructans from bat wing skin and soil, for cryopreserving the fungus, and for preparing liquid suspensions for laboratory experimentation. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Isolating Pseudogymnoascus destructans from bat wing skin Basic Protocol 2 : Isolating Pseudogymnoascus destructans from soil Basic Protocol 3 : Cryopreservation of Pseudogymnoascus destructans Basic Protocol 4 : Preparing liquid conidial suspension of Pseudogymnoascus destructans